Historien som scene hos Ludvig Holberg og Charlotta Dorothea Biehl - Mai, Anne-Marie (1700-tal: Nordic Journal for Eighteenth-Century Studies, 2011)
Ludvig Holberg (1684-1754) and Charlotta Dorothea Biehl (1731-1788) are two key figures of the Nordic Enlightenment. The Norwegian Holberg took his philosophical and theological degrees from the University of Copenhagen at an early age and travelled around Europe accumulating knowledge for his historical writings. Holberg made a splendid career at the University of Copenhagen both as a professor and vice-chancellor and published historical works, satires, comedies, essays, fables, and autobiographical letters. As a woman, Biehl was barred from university education and public office. Her world was confined to her childhood home, and she never had the opportunity to travel. In return, she immersed herself in studies of language and theatre, reading with great enthusiasm Holberg's writings. She became a comedy writer and a novelist, and also wrote historical works and historical letters. The paper discusses how Biehl and Holberg made performing arts and historiography inspire each other. History is in their depictions not only a royal chronology, but a vivid narrative. Holberg's and Biehl's approaches to historical study drew on different traditions: Holberg was influenced by ancient historiography while Biehl was inspired by the French chronicle; therefore, their historical writings have very different contents and designs.
Keywords: historiography; theatre; history; narration